Repositioning Artificial Intelligence as a Core Enabler of Educational and Entrepreneurial Ecosystems in Nigeria - Adelakun, Najeem Olawale; Mande, Samaila (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2027)
This study investigates Artificial Intelligence (AI) as a catalyst for integrating Nigeria’s educational and entrepreneurial ecosystems to mitigate engineering graduate unemployment. Employing a structured questionnaire, primary and secondary data were collected to evaluate AI's impact on entrepreneurial clusters, enabling environments, and workforce retention. Findings reveal that AI significantly enhances employability by identifying skill gaps and fostering mentorship. Furthermore, within entrepreneurial ecosystems, AI improves opportunity recognition, resource optimization, and cluster-based innovation. The discussion highlights that AI-driven retention strategies effectively minimize skills attrition by embedding graduates within adaptive, locally relevant enterprises. In conclusion, integrating AI into academic curricula and ecosystem policy frameworks is an urgent strategic imperative to unlock human capital, reduce unemployment, and foster sustainable economic growth in Nigeria.